Laparoscopic Assisted Orchidectomy Eases Future Insertion of Testicular Prosthesis in Paediatric Patients - Abdul Aziz, Dayang Anita; Abidin, Zainal Adwin; Nor, Mahmud Mohd; Md Pauzi, Suria Hayati; Rasat, Rahmah; Latiff, Zarina Abdul (Bangladesh Journal of Endosurgery, 2014)
High ligation orchidectomy in paediatric patients is performed for testicular tumours. This is carried out via open surgery at the inguinal or groin region. In these boys, elective insertion of testicular prostheses is carried out later to improve the external genitalia appearance. In most cases, insertion of testicular prosthesis or implant is carried out via the previous scar, to avoid prosthesis extrusion; however this is usually difficult due to scarring and may cause haematoma and possible infection. We report a novel technique of laparoscopic assisted orchidectomy in an adolescent boy with disorder of sexual development (DSD) whom was suspected of having bilateral gonadal (testicular) malignant change, he successfully underwent bilateral ligation of testicular vessels laparoscopically and removal of both testes via a midline scrotal raphe incision; hence avoiding bilateral groin incisions. With this method, future insertion of testicular prostheses can be carried out via virgin inguinal incisions.